1974
DOI: 10.1007/bf01219672
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the mechanism of L-leucine- and ?-ketoisocaproic acid ? Induced insulin release from perifused isolated pancreatic islets

Abstract: The insulinotropic effects of L-leucine and e-ketoisocaproic acid have been compared in perifused isolated pancreatic islets. In contrast to e-ketoisocaproic acid (10 mM), L-leucine (10 raM) released less insulin in the presence than in the absence of glucose (5 mM). Changes of islet cell metabolism accompanying insulin release were studied by recording the fluorescence of reduced pyridine nucleotides. The traces of L-leucine-or e-ketoisocaproic acid-induced fluorescence increase differed both in the absence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
2
1

Year Published

1975
1975
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 9 publications
(10 reference statements)
2
27
2
1
Order By: Relevance
“…An increase in the extent of reduction of nicotinamide nucleotides in intact perifused islets of Langerhans was observed when the concentration of glucose in the perifusion medium was increased from 3 to 20mM (Panten et al, 1973). Such changes have been correlated with rates of insulin release under various conditions (Panten et al, 1973(Panten et al, , 1974. However, with the technique used, it was not possible ascertain the cellular location and identity of the reduced nicotinamide nucleotides.…”
mentioning
confidence: 95%
“…An increase in the extent of reduction of nicotinamide nucleotides in intact perifused islets of Langerhans was observed when the concentration of glucose in the perifusion medium was increased from 3 to 20mM (Panten et al, 1973). Such changes have been correlated with rates of insulin release under various conditions (Panten et al, 1973(Panten et al, , 1974. However, with the technique used, it was not possible ascertain the cellular location and identity of the reduced nicotinamide nucleotides.…”
mentioning
confidence: 95%
“…KIC is an endogenous substrate of the Krebs' cycle arising from the oxidative deamination of leucine. When applied externally, KIC permeates the plasmalemma and the mitochondrial membrane, thereby providing direct activation of the Krebs cycle and enhancing ATP production (45,46); the subsequent rise in the cytosolic ATP/ADP ratio is the proposed mechanism by which KIC inhibits K-ATP channels, stimulates the electrical activity, and elicits insulin release in a manner entirely similar to glucose (47). In this study, stimulation of the cells was provided by adding 30 mM KIC to the perifusion solution for specified periods; the pH i and the [Ca 2ϩ ] i were recorded from single cells which have been double-labeled with BCECF and fura-2. ]…”
Section: Effect Of Kic On the Ph I And [Ca 2ϩmentioning
confidence: 99%
“…Effects on K ATP Channel Activity by L-Leucine and 2-Oxopentanoate-Several studies have described insulinotrophic effects of L-leucine (3,20,21). Because of the blocking effect of ␣-ketoisocaproate on the K ATP channel, we also investigated whether the precursor amino acid, L-leucine, had direct effects on the channel in excised patches.…”
Section: Atp-dependent Kmentioning
confidence: 99%
“…1 An increase in mitochondrial metabolism plays an important role in the response to glucose and several other fuel secretagogues. Among other fuel secretagogues, the deamination product of the amino acid L-leucine, ␣-ketoisocaproate, is of particular interest since it is exclusively metabolized in mitochondria (3,4). Accordingly, several studies have shown that ␣-ketoisocaproate stimulates insulin secretion (3,4), initiates electrical activity (5), and inhibits the ␤-cell K ATP channel in intact cells monitored in the cell-attached configuration of the patch-clamp technique (6 -8).…”
mentioning
confidence: 99%
See 1 more Smart Citation